Understanding CDA: Histories, Remembering, And Futures - Siti Rafiah (Script Journal: Journal of Linguistics and English Teaching, 2018)
The aim of this library research article is trying to give us a deep understanding of what Critical Discourse Analysis is. The article starts with a discussion of the origin of Critical Discourse Analysis (CDA), then exploring interdisciplinary based on the theory proposed by Fairclough renowned expert in DA field, in the last part of the article discussed the principles of CDA form Fairclough point of view. The present article uses a descriptive qualitative approach from reputable references which is relevant to the topics.Â